Study of Rotational Motions Caused by Multiple Mining Blasts Recorded by Different Types of Rotational Seismometers - Krzysztof P. Teisseyre; Michał Dudek; Leszek R. Jaroszewicz; Anna T. Kurzych; Leopold Stempowski (Sensors, 2021)
Digging two vertical shafts with the multiple blasts technique gave the opportunity to measure the induced angular motions in a horizontal plane with well-defined positions of sources. Three kinds of rotation rate sensors, sharing an underground location, were used. Two of them—a Fiber-Optic System for Rotational Events & phenomena Monitoring (FOSREM) and a prototypical seismometer housing the liquid-filled torus—sensed the rotation, while a microarray of two double-pendulum seismometers sensed both the rotation and symmetric strain. The FOSREM was sampled at 656.168 Hz, while all the others were only sampled at 100 Hz. There were considerable differences within the results gathered from the mining blasts, which should be attributed to two causes. The first one is the difference in principles of the operation and sampling rates of the devices used, while the other is the complex and spatially variable character of the studied wave fields. Additionally, we established that the liquid-filled sensor, due to its relatively low sensitivity, proved to be viable only during a registration of strong ground motions. Overall, a comparative study of three different rotational seismometers was performed during mining-induced strong ground motions with well-localized sources.